2015
DOI: 10.1128/iai.02904-14
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Yersiniabactin Import Attenuates Extraintestinal Pathogenic Escherichia coli in Cystitis and Pyelonephritis and Represents a Novel Target To Prevent Urinary Tract Infection

Abstract: The emergence and spread of extended-spectrum beta-lactamases and carbapenemases among common bacterial pathogens are threatening our ability to treat routine hospital-and community-acquired infections. With the pipeline for new antibiotics virtually empty, there is an urgent need to develop novel therapeutics. Bacteria require iron to establish infection, and specialized pathogen-associated iron acquisition systems like yersiniabactin, common among pathogenic species in the family Enterobacteriaceae, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 49 publications
2
41
0
Order By: Relevance
“…A recent study using a fyuA-deficient UPEC strain found that it had a competitive defect in the bladder weaker than that observed for the ybtPQ-deficient UPEC strain in the present study. In contrast, the defect in infections with a single strain was somewhat more pronounced for fyuA mutants than ybtPQ mutants (29,(47)(48)(49)(50). A previous study using a tonB-deficient UPEC strain yielded results similar to those obtained with the fyuA mutant (51).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…A recent study using a fyuA-deficient UPEC strain found that it had a competitive defect in the bladder weaker than that observed for the ybtPQ-deficient UPEC strain in the present study. In contrast, the defect in infections with a single strain was somewhat more pronounced for fyuA mutants than ybtPQ mutants (29,(47)(48)(49)(50). A previous study using a tonB-deficient UPEC strain yielded results similar to those obtained with the fyuA mutant (51).…”
Section: Discussionmentioning
confidence: 49%
“…The overall expression of the yersiniabactin system can be inferred by evidence of yersiniabactin biosynthesis as well as serological and transcriptional evidence of ybtP, ybtQ, and fyuA expression during mouse and human cystitis (17,(27)(28)(29). Beyond UTIs, ybtPQ mutants of Yersinia pestis and Klebsiella pneumoniae exhibit diminished virulence in mouse models of bubonic plague and pneumonia, respectively (14,30).…”
mentioning
confidence: 99%
“…It is highly prevalent among clinical extraintestinal pathogenic E. coli isolates and is also found with varying frequencies in other Enterobacteriaceae, including the eponymous Yersinia pestis (18). Yersinia HPI genes are highly upregulated during UTI, and Ybt is detectable in patients' urine specimens (12,14,17). Ybt, the recognized product of Yersinia HPI-positive bacteria to date, has been distinguished from other E. coli siderophores by its ability to form stable Cu(II) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that the early stages of ascending UTI are competitive and favor isolates with specific siderophore profiles. In this and other studies, Ybt, a siderophore encoded by the Yersinia high pathogenicity island (HPI), was associated with urinary tract virulence (7,(13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…Prominent among these is the Yersinia high pathogenicity island (HPI), which encodes the biosynthetic machinery to make the specialized metabolites yersiniabactin (Ybt) and escherichelin (2). Direct mass spectrometric detection of urinary Ybt in UTI patients, serological markers, transcriptional signatures, and experimental infection models all indicate active expression of Yersinia HPI proteins during UTI pathogenesis (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%